CSR INTEGRATION INTO THE CORPORATE STRATEGY - Patrizia GAZZOLA; Gianluca COLOMBO (Cross-Cultural Management Journal, 2014)

(untitled)
The aim of this research paper is to develop a model for the integration of ethics and Corporate Social Responsibility (CSR) into the company strategy as a source of competitive advantages. CSR is an organization's obligation to consider the interests of their customers, employees, shareholders, communities and to consider the social and environmental consequences of their business activities. By integrating CSR into the corporate strategy and stakeholder management, organizations can ensure that the increasing of shareholder value doesn’t overshadow the need to behave ethically to their stakeholders. The research is based on the theoretical framework that supports a thesis of beneficial impact of the development and implementation of CSR plan: by planning out CSR as part of a corporate strategy, companies can achieve the ultimate goal of creating both social value and corporate value.